Functionalized ionic-liquid templated mesoporous silica nanoparticles for anticancer drug delivery system - Zaharudin, Nurul Syahira (2018)
Over the recent decades, mesoporous silica nanoparticles (MSNs) have been studied as one of the most promising approaches for drug delivery systems in order to overcome the limitations of conventional cancer therapies. Their versatile properties such as stability, tuneable physical characteristics, great biocompatibility, and easy functionalization make them the suitable candidates for this approach. Typical synthesis of MSNs involves solvents, silica precursor, acid or base as catalyst, and surfactant as the templates. Currently the most established template to generate MSNs is anionic surfactants such as cetrimonium bromide (CTAB). Nevertheless, the template materials for MSNs synthesis are now no longer limited to anionic surfactants due to the recent discovery of ionic liquids (ILs). This is due to the similar core structure of ILs with cetrimonium bromide in which both consist of inorganic or organic anions and bulky organic cations. One of the pros of ILs is the diverse combinations of cations and anions that can transform the physical features of ILs. Our previous research have successfully synthesized monodispersed MSNs by using a series of pyridinium salts IL with different alkyl chain lengths (CnPyBr where n = 12, 14, 16, and 18). The MSNs synthesized with 16-carbon pyridinium IL named 1- hexadecylpyridinium bromide (C16PyBr) give the best monodispersity among others, as well as large surface area. The MSNs synthesized with the C16PyBr IL exhibits comparable huge surface area (<700 m2/g), high pore volume (<1 cm3/g) and tuneable pore size (~7-10 nm) with the MSNs synthesized using CTAB. Therefore, in this work the C16PyBr IL templated MSNs were functionalized to develop a controlled drug delivery system. The mesoporous silica materials with spherical morphology and uniform particles and pore size were synthesized by using C16PyBr IL as the template and modified with 3–aminopropyltriethoxysilane (APTES), 3– mercaptopropyltrimethoxysilane (MPTMS) and succinic anhydride via post – grafting method in to get MSN – NH2, MSN – SH and MSN – COOH as drug carrier, respectively. The mesoporous structure of the modified MSNs were entirely characterized by transmission electron microspcopy (TEM), N2 sorption isotherm, Fourier transform infrared (FTIR), X – ray diffraction (XRD), thermogravimetry analysis (TGA) and zeta potential. The bare MSNs as well as the functionalized MSNs are amorphous and displayed type IV BET isotherms with H2 hysteresis loop which is a typical isotherm for mesoporous materials. The surface area of the bare MSNs (730 m2/g) also shows a drastic reduction after functionalized of the silica surface with the organic groups. The TEM images show that the size and shape of the MSNs remains unchanged after post-grafting functionalization have been done. A comparative study of the uptake and release of two model drugs, quercetin and gemcitabine were carried out, where quercetin shows higher degree of drug loaded compared to gemcitabine due to the better interaction of the silica surface with drug molecule. Overall, it was observed that the functionalized MSNs show higher degree of drugs uptake and slower release compared to the bare MSN. The percentage loading for quercetin by bare MSN, MSN-NH2, MSN-COOH and MSN-SH is 45%, 72%, 50% and 63%, respectively. Meanwhile, for gemcitabine the loading percentage is as follows; bare MSN (24%), MSN-NH2 (32%), MSN-COOH (45%), and MSN-SH (39%). Drug release study was conducted for 48 hours, and only 30% of quercetin and 33% of gemcitabine has been released by bare MSNs. Much slower releases were observed for all functionalized MSNs for both drugs. Hence, from the in vitro studies it can be conclude that MSNNH2 and MSN-COOH are good drug carriers for quercetin and gemcitabine, respectively. Surface functionalization of the MSNs affected the uptake and release process of drugs due to the interaction of the different functional groups on the MSNs with the drugs. Drugs release kinetics study indicated that the release process follows the zero order and Higuchi model. In this study, it is suggested that MSNs with surface functionalization have appropriate properties for controlled drug release which give steady release behaviour over a period of time to avoid repetitive administration of drug. Meanwhile, the non-functionalized MSNs will be a suitable candidate to use as a carrier for analgesics or anti-inflammatory agents for fast release system.